Calcitriol (1,25-dihydroxycholecalciferol) selectively inhibits proliferation of freshly isolated tumor-derived endothelial cells and induces apoptosis - Flynn, G.; Chung, I.; Yu, W.D.; Romano, M.; Modzelewski, R.A.; Johnson, C.S.; Trump, D.L. (2006)
Calcitriol (1,25-dihydroxycholecalciferol) has antiproliferative and/or proapoptotic effects on many cell types and the glucocorticoid dexamethasone enhances these effects. We have shown that calcitriol modulates several key signaling proteins involved in differentiation, proliferation and apoptosis in tumor-derived murine endothelial cells (TDEC) and that these effects were not seen with endothelial cells isolated similarly from normal tissues. In the present study, TDEC and mouse embryonic yolk sac endothelial cells (MYSEC) were treated with calcitriol and followed over time for an effect. MYSEC were utilized as 'normal' control endothelial cells because they were more primitive, being isolated from a highly neovascular tissue, and had a similar morphology without the stimulus of the tumor microenvironment. The vitamin D receptor (VDR) is present in TDEC and MYSEC, and was upregulated in calcitriol-treated TDEC and MYSEC; dexamethasone further increased VDR expression following 48 h of treatment. The modulatory effects on signaling proteins were maximal by treatment for 48 h; phospho-Erk, phospho-Akt, p21 and bcl-2 were decreased in treated TDEC with the induction of p27 but there were no effects on MYSEC. After 48 h increased apoptosis was seen in treated TDEC by annexin V labeling with caspase-3 cleavage and decreased levels of poly(ADP-ribose) polymerase, but no effects were seen in MYSEC. Cell cycle analysis showed increased G(0)/G(1) arrest and an increase in the apoptotic sub-G 1 peak in treated TDEC but similar effects were not seen in MYSEC following 48-hour treatment. Proliferation assays were utilized and TDEC demonstrated decreased proliferation compared to normal endothelial cells at 48 h. To determine whether or not the VDR signaling was impaired in MYSEC, we performed the 24-hydroxylase (CYP24) promoter-luciferase reporter assay. CYP24 is a key enzyme involved in the breakdown of vitamin D. VDR signaling was intact in both cell types and calcitriol induced CYP24 mRNA expression in MYSEC but not in TDEC. Taken together, despite similar levels of VDR expression and intact signaling in both cell types, calcitriol selectively inhibits proliferation and induces apoptosis in TDEC with no effect on MYSEC. Thus calcitriol exerts differential effects on TDEC compared to normal cells. Copyright (c) 2006 S. Karger AG, Basel